IKM DAN DIAGRAM KARTESIUS : KUALITAS PELAYANAN PDAM KOTA PONTIANAK PADA MASA PANDEMI COVID-19 - Ana Yuliana; Udin Rinaldi (Jurnal Ekonomi Integra, 2021)
The research objective was to analyze the community satisfaction index (IKM) regarding the service quality of PDAM Pontianak City including the service standards carried out during the new normal transition based on Law  no. 19 of 2020. The qualitative descriptive research method uses primary data in the form of 100 customers taken purposively. Research indicators based on Law no. 25 of 2009. The analysis tool uses the IKM analysis and Cartesian diagrams. The results of the study found that based on the IKM analysis, the indicators that were not optimal were the speed of service, service procedures and implementation schedule. Based on Cartesian analysis found major improvements in service procedures and clarity of officers, as well as additional improvements in the form of service speed, fairness of service costs and certainty of service schedules